The effect of intensity and rolling resistance on inner-cycle temporal parameters when roller-ski skating - Meyer, F.; Kocbach, J.; Seeberg, T. M.; Lund-Hansen, M.; Austeng, A.; Sandbakk, Ø. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
INTRODUCTION: The continuous development of wearable sensor technology allows technologies previously used in research settings to be applied for technical analysis of regular training sessions. The aim of this study was to investigate the effect of intensity and rolling resistance on inner-cycle temporal parameters measured by instrumented insoles and poles when roller ski skating.